Opportunistically acquired evidence is unsuitable data to model fox (Vulpes vulpes) distribution in Tasmania. (24th June 2014) - Marks, Clive A.; Obendorf, David; Pereira, Filipe; Edwards, Ivo; Hall, Graham P.
ABSTRACT Despite the absence of direct observation of live foxes in the Tasmanian environment, a recent study concluded that foxes are now widespread on the island and proposed a habitat‐specific model incorporating 9 cases of physical evidence presumed to confirm their unique presence. We briefly review the history of fox incursions into Tasmania and then assess the quality of putative physical evidence against a defined evidentiary standard. Overall, 14 of 17 incidents described since 1998 were associated with between 1 and 4 criteria indicative of unreliable data or were not associated with adequately documented physical evidence. Anonymous and anecdotal information was fully or partially relied upon in 10 of 17 cases and of these 5 were widely acknowledged to be hoaxes. We conclude that opportunistically acquired evidence is a poor substitute for data obtained by properly designed and independent wildlife surveys for confirming unique fox incursions and as the basis of ecological models predicting true habitat‐specific fox distribution. Species rarity decreases the reliability of wildlife surveys and population models; thus validation of unique incursions in particular requires appropriate rigor in evidentiary standards and data quality. Precautionary management that may be considered in response to uncertain information, or opportunistically collected specimens of doubtful provenance, does not imply that such information should be treated as scientific data. We suggest that an eradication program is justified as a precautionary measure only after rigorous qualitative analysis reveals data capable of rejecting the null hypothesis that the species of interest is absent. © 2014 The Wildlife Society.